RESEARCH OF STRUCTURAL PREPARATION BROCHETS IN THE MACHINING OF CYLINDRICAL HOLES - TELYATNIK, INNA; PALADIYCHUK, YURIY; HOROVYI, ARTUR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In modern mechanical engineering, machining of cylindrical holes with high precision and surface quality is a critically important stage in the production of many parts. Broaching is one of the highly effective methods of finishing such holes, which allows achieving high productivity and accuracy of geometric parameters. However, traditional solid broaches have certain limitations associated with the complexity of manufacturing, high cost, limited possibilities for optimizing the geometry of cutting elements for different materials and processing modes, as well as the complexity of repair in case of damage to individual teeth. In this regard, the current scientific and technical task is the development and study of the effectiveness of structural prefabricated broaches for machining cylindrical holes. The proposed work is devoted to solving this problem through a comprehensive approach, which includes theoretical analysis of the broaching process using prefabricated tools, development of new designs of such broaches taking into account optimization of the geometry of cutting elements, experimental studies to assess their impact on key parameters of the machining process, namely: accuracy of geometric dimensions and shape of holes, roughness of the machined surface, process productivity and tool stability. The study will analyze existing broaches designs and identify their advantages and disadvantages. Based on this analysis, new design solutions for prefabricated broaches will be proposed, which provide for the possibility of quick replacement of individual cutting sections or teeth, optimization of cutting angles and other geometric parameters for different stages of machining (roughing, semi-finishing and finishing), as well as the possibility of using different materials for cutting elements depending on the material being machined and surface quality requirements.